STUDI ETNOMATEMATIKA: KAIN BERBAHAN DASAR HALAL DITINJAU DARI MOTIF SADULUR BATIK LEBAK PROVINSI BANTEN - Andri Imam Subekhi; Swastika Oktavia (International Journal Mathla’ul Anwar of Halal Issues, 2021)
Ethnomatematics is mathematics that is contained in culture. The purpose of this research is to examine the material of the sadulur batik lebak banten motif through aspects of halal products. The research method used is a qualitative method with an ethnographic approach. The data collection techniques used are literature study, interviews and documentation. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. Data validity checks were carried out by extending observations, increasing persistence, using reference materials. The result of this research is that in the batik sadulur motif of lebak banten, there is a halal aspect of the material used in the form of batik cloth, the equipment used such as cloth, chanting and coloring.